Néel‐Type Elliptical Skyrmions in a Laterally Asymmetric Magnetic Multilayer. Issue 12 (18th February 2021) - Cui, Baoshan; Yu, Dongxing; Shao, Ziji; Liu, Yizhou; Wu, Hao; Nan, Pengfei; Zhu, Zengtai; Wu, Chuangwen; Guo, Tengyu; Chen, Peng; Zhou, Heng‐An; Xi, Li; et al.
Abstract: Magnetic skyrmions, topological‐chiral spin textures, have potential applications in next‐generation high‐density and energy‐efficient spintronic devices for information storage and logic technologies. Tailoring the detailed spin textures of skyrmions is of pivotal importance for tuning skyrmion dynamics, which is one of the key factors for the design of skyrmionic devices. Here, the direct observation of parallel aligned elliptical magnetic skyrmions in Pt/Co/Ta multilayers with an oblique‐angle deposited Co layer is reported. Domain wall velocity and spin–orbit‐torque‐induced out‐of‐plane effective field analysis demonstrate that the formation of unusual elliptical skyrmions is correlated to the anisotropic effective perpendicular magnetic anisotropy energy density ( K eff u ) and Dzyaloshinskii–Moriya interaction (DMI) in the film plane. Structural analysis and first‐principles calculations further show that the anisotropic K eff u and DMI originate from the interfacial anisotropic strain introduced by the oblique‐angle deposition. The work provides a method to tune the spin textures of skyrmions in magnetic multilayers and, thereby, a new degree of freedom for the design of skyrmionic devices. Abstract : Néel‐type elliptical magnetic skyrmions are observed in Pt/Co/Ta multilayers with an oblique‐angle deposited Co layer. The formation of elliptical skyrmions is found to be related to the anisotropic effective perpendicular magnetic anisotropy energy density and Dzyaloshinskii–Moriya interaction in the film plane. The results provide a route to tuning the symmetry of skyrmions for related physics study and device applications.